2019
DOI: 10.1111/ina.12600
|View full text |Cite
|
Sign up to set email alerts
|

Associations between evaporative cooling and dust‐mite allergens, endotoxins, and β‐(1 → 3)‐d‐glucans in house dust: A study of low‐income homes

Abstract: Recent work suggests that evaporative coolers increase the level and diversity of bioaerosols, but this association remains understudied in low‐income homes. We conducted a cross‐sectional study of metropolitan, low‐income homes in Utah with evaporative coolers (n = 20) and central air conditioners (n = 28). Dust samples (N = 147) were collected from four locations in each home and analyzed for dust‐mite allergens Der p1 and Der f1, endotoxins, and β‐(1 → 3)‐d‐glucans. In all sample locations combined, Der p1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 73 publications
(157 reference statements)
1
9
0
Order By: Relevance
“…However, allergen levels, with the exception of one sample, were again below the sensitization threshold. In a subsequent study of low‐income homes in Utah County, Utah, Johnston et al (2019) found Der p 1 or Der f 1 in house dust was significantly higher in EC ( n = 20) compared to AC ( n = 28) homes (OR = 2.29; 95% CI: 1.05, 4.98; p = 0.04) 93 . The authors also found a higher prevalence of dust mite allergens in EC (55%) compared to AC homes (36%).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, allergen levels, with the exception of one sample, were again below the sensitization threshold. In a subsequent study of low‐income homes in Utah County, Utah, Johnston et al (2019) found Der p 1 or Der f 1 in house dust was significantly higher in EC ( n = 20) compared to AC ( n = 28) homes (OR = 2.29; 95% CI: 1.05, 4.98; p = 0.04) 93 . The authors also found a higher prevalence of dust mite allergens in EC (55%) compared to AC homes (36%).…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that the Sneller & Pinnas and Lemons et al studies did not specifically measure β‐(1 → 3)‐D‐glucan levels so that remains unknown. A recent study of low‐income homes in Utah (USA) by Johnston et al (2019) found house dust β‐(1 → 3)‐D‐glucan concentration (μg/mg) and surface load (μg/m 2 ) were 2.65‐fold and 3.64‐fold higher, respectively, in EC ( n = 20) compared to AC ( n = 28) homes 93 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations